Copyright Fraud in the Internet Age: Copyright Management Information for Non-Digital Works Under the Digital Millennium Copyright Act - Jacobs, Russell W. (Science and Technology Law Review, 2012)
With the advent of the digital age, authors of creative works enjoy the benefits of quickly and inexpensively distributing their works to global audiences. These developments have unfortunately led to the negative consequence that pirated, unauthorized, or altered copies reach potential users before the creator of the work releases the authentic version according to his or her terms. The Digital Millennium Copyright Act of 1998 sought to address some of these concerns by punishing circumventions of technologies controlling access to copyrighted works (17 U.S.C. § 1201) and by protecting “copyright management information,” i.e. the data identifying the author and the terms of use of a copyrighted work (17 U.S.C. § 1202). While scholars have commented extensively on section 1201, little scholarship exists on section 1202. This Article addresses that gap. The Article discusses a federal court split regarding the scope of application of section 1202 and demonstrates that the legislative history and the plain language of the statute call for broad application to both digital and non-digital works. The Article then looks at section 1202 in the context of Internet fraud, and argues that this section functions as a consumer fraud statute, offering protections for the provision of accurate information and authentic works that can well serve copyright owners and consumers.